Mulheres negras e ressignificação de políticas públicas - Barbosa, Eliete Edwiges (2022)
This thesis deals with the resignification of the meanings of public policies made by black women who develop social actions in peripheral communities in the metropolitan region of São Paulo. For this, it makes a theoretical review of the concept, formulation and analysis of public policies in order to problematize them with the singularity of the Brazilian reality marked by late regulation and the inexistence of a Welfare State. In addition, the theme of racism and machismo was focused on from the racialized territorial distribution of urban space, which generated a racialized access to citizenship rights. Finally, through semi-structured interviews carried out with black women who develop social actions in peripheral territories of the metropolitan region of São Paulo, the mechanisms of appropriation and resignification of public policies were detected, signaling the need to rethink the mechanisms of formulation and evaluation of public policies